Effects of Ni content on the microstructure and properties of laser powder bed fusion-processed Fe–18Cr–XNi alloys - Yongchao Lu; Xiaoqun Li; Yazhou He; Yaqing Hou; Fafa Li; Yao Lu; Hao Zhang; Lanting Zhang; Hong Wang; Hang Su (Journal of Materials Research and Technology)
Alloys such as 304L and 316L have been widely used as base materials for LPBF process development, component fabrication, and materials research. However, the specific influence of Ni, a key element in these alloys, on the microstructure and properties of LPBF-fabricated components remains underexplored. This study investigates the evolution of microstructure and performance in Fe–18Cr–XNi alloys under identical LPBF processing conditions as a function of Ni content. A phase transformation from BCC (2–4Ni) to BCC + FCC (6–10Ni), and finally to FCC (12Ni), was observed. Thermodynamic calculations indicate that the phases present correspond to those predicted for equilibrium conditions in the high-temperature range of 1250°C–1350 °C. Grain morphology transitioned from columnar (2–4Ni) to equiaxed (6–9Ni), and back to columnar (10–12Ni). The results indicate that columnar grains form in the single-phase region due to epitaxial growth, while the second phase's distribution and proportion in the dual-phase region promote equiaxed grain formation. Additionally, non-equilibrium simulations indicate that differences in supercooling due to Ni addition may correlate with the final grain size. Influenced by these microstructural changes, the alloy's hardness initially increases and then decreases, reaching a peak of 293 HV at 6Ni due to fine-grain strengthening. This work provides a fundamental reference for composition tuning and performance optimization of widely used 300-series alloys in LPBF research.